2008
DOI: 10.1007/s00103-008-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Biologische Belastungen in der Arbeitswelt

Abstract: Infections are a common occupational hazard, especially in health care (and laboratory) workers, but also for the staff of daycare centers, food handlers, forestry and agricultural workers and persons occupied in waste management and sewage work. EC directives and national German regulations have been implemented to facilitate risk assessment, risk management and prevention of infections. In this contribution, the classification of microbiological agents and their seroprevalence (or one of their antibodies) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…Other studies have shown that day care centre workers and school teachers in close contact with children are more often exposed to infections in the workplace [30]. Infectious agents like Cytomegalovirus and Parvovirus B19 have been shown to frequently affect women who work with children [31], but we did not find an excess risk of any adverse pregnancy outcome in this group.…”
Section: Discussioncontrasting
confidence: 76%
“…Other studies have shown that day care centre workers and school teachers in close contact with children are more often exposed to infections in the workplace [30]. Infectious agents like Cytomegalovirus and Parvovirus B19 have been shown to frequently affect women who work with children [31], but we did not find an excess risk of any adverse pregnancy outcome in this group.…”
Section: Discussioncontrasting
confidence: 76%